Corrosion Under Insulation Probability of Failure Prediction Framework Accordance with API 581 - S. F. Yeow; A. R. Othman; M. Mohammad; S. B. Mohammad Agil (International Journal of Integrated Engineering, 2026)
This paper proposed a framework for prediction of corrosion under insulation (CUI) probability of failure (PoF) based on the risk-based inspection (RBI) methodology outlines in API 581. Despite the advancement of CUI inspection technologies and prediction methods available, there are still limitations leading to uncertainties in CUI predictions. This is due to CUI occurrence that is influenced by many factors besides the presence of moisture and operating temperatures. API 581 guidelines in PoF calculation integrate many CUI contributing factors compared to other available industrial standards, making it a more holistic and conservative approach for CUI potential failure prediction. The framework proposed in this paper is an improvised version from the API 581 approach which provides a focused and localized approach in identification of potential CUI failure risk. This framework provides different PoF values for different areas within a piping line analyzed ranging from 0 to 1. A sample analysis for one piping line isometrics yields predicted PoF values ranging from 0.0003 to 0.5630 for piping configuration across the entire piping lines with multiple conditions in the CUI contributing factors. The results provide a guideline for plant owners to optimize CUI maintenance planning by prioritizing areas with higher PoF values, indicating higher risk.